Simulation Analysis and Test of Pneumatic Distribution Fertilizer Discharge System - Biao Cheng; Ruiyin He; Yong Xu; Xuzheng Zhang (Agronomy, 2022)
Precision fertilizer application technology is necessary to improve the utilization efficiency of fertilizers in agricultural production. Traditional mechanical fertilization systems risk blockages and uneven application when working in multiple crop rows. Pneumatic fertilization systems have improved efficiency and fertilization quality, however, fewer studies have characterized their designs in regards to the motion of the fertilizer particles. Here, we design and evaluate the parameters of the key components of a pneumatic fertilizer discharge system. Numerical simulations were conducted using a coupled EDEM-FLUENT and gas-phase models together with bench tests to examine the effects of inlet wind speed on the efficiency and consistency of the pneumatic fertilization system. The EDEM-FLUENT simulations showed that the number of fertilizer particles in the grid box set by EDEM was 60 particles in the range from t = 0.275 s to t = 0.5 s, and there was no blockage or cut-off in the pipe. The gas-phase simulation showed that there were tiny vortices in the fertilizer conveying pipe, and the maximum flow rate of its backflow was lower than 3.59 m/s, which had little effect on the fertilizer conveyance. The bench test showed that the inlet wind speed was 35–40 m/s, and the fertilization efficiency was 0.29–0.41 kg/s when the maximum variation coefficient of the row discharge consistency of the pneumatic distribution fertilizer discharge system was 5.55%. The coefficient of variation of the average row discharge consistency was 3.93%, and the average fertilizer discharge met the design requirements. Therefore, the pneumatic distribution system achieves stable operation and meets the requirements of fertilization operations.